2022
DOI: 10.1130/g49544.1
|View full text |Cite
|
Sign up to set email alerts
|

Multi-proxy evidence of Caribbean-sourced marine incursions in the Neogene of Western Amazonia, Brazil

Abstract: The timing of continental-scale marine flooding events in Western Amazonia during the Neogene is still an unsolved question. Despite broad proxy-based evidence of such events, the pathways and duration of late Miocene marine incursions remain controversial. We provide coupled calcareous and organic microfossil and geochemical data from six onshore cores from Neogene sequences of the Solimões Basin, Brazil. Our records support minor marine influence in the early Miocene (23.0, 21.1, 18.6, and 16.3 Ma), middle M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Eighty-four cores were drilled in the Solimões Basin (Figure 2), representing the only continuous and high-quality sedimentary archive for this region to date. These cores, combined with outcrop data, provided a basis for multiple palynological and lithological studies that permitted relative age determination of the sediments, paleoecological and paleoenvironmental reconstructions (e.g., Hoorn 1993;Da Silva-Caminha et al 2010;Jaramillo et al 2010Jaramillo et al , 2017d'Apolito 2016, Leite et al 2017, 2021Linhares et al 2017Linhares et al , 2019Leandro et al 2019Leandro et al , 2022d'Apolito et al 2021) (Supplemental Table 2), provenance analyses (Andean or Amazon source), and absolute age determination of the sediments based on isotope data (Roddaz et al 2005, Horbe et al 2019, Kern et al 2020. A schematic overview of the lithology, sediment ages, and phytogeographic and interpretation through time is presented in Figure 3.…”
Section: Insights Into Deep Time Amazonian Florasmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighty-four cores were drilled in the Solimões Basin (Figure 2), representing the only continuous and high-quality sedimentary archive for this region to date. These cores, combined with outcrop data, provided a basis for multiple palynological and lithological studies that permitted relative age determination of the sediments, paleoecological and paleoenvironmental reconstructions (e.g., Hoorn 1993;Da Silva-Caminha et al 2010;Jaramillo et al 2010Jaramillo et al , 2017d'Apolito 2016, Leite et al 2017, 2021Linhares et al 2017Linhares et al , 2019Leandro et al 2019Leandro et al , 2022d'Apolito et al 2021) (Supplemental Table 2), provenance analyses (Andean or Amazon source), and absolute age determination of the sediments based on isotope data (Roddaz et al 2005, Horbe et al 2019, Kern et al 2020. A schematic overview of the lithology, sediment ages, and phytogeographic and interpretation through time is presented in Figure 3.…”
Section: Insights Into Deep Time Amazonian Florasmentioning
confidence: 99%
“…In the Amazon, the biostratigraphy shows conflicting patterns (see Latrubesse et al 2007, d'Apolito 2016, Leite et al 2021, Leandro et al 2022) that can be explained by the multiple dispersal events that are reported for the Neotropics (Antonelli et al 2018). While the Amazon is a source of biodiversity (Antonelli et al 2018), the fossil record in northern South America shows that the region also received many species from other localities through dispersal events (e.g., Germeraad et al 1968).…”
Section: Insights Into Deep Time Amazonian Florasmentioning
confidence: 99%
See 1 more Smart Citation
“…In periods of relative sea‐level rise, coastal systems are inundated and displaced inland, resulting in a retrogradation pattern. In extreme cases of sea‐level rise, the inundation of continental regions may generate vast epicontinental seas such as the middle Miocene transgression that formed the Paranaense‐Entrerriense Seas over the La Plata basin and the Pebas system in the Amazon (Aumond et al., 2021; Del Río et al., 2018; Leandro et al., 2022; Ruskin et al., 2011). On the contrary, in periods of sea‐level fall, coastal systems prograde over the continental platform, whereas fluvial systems may migrate over the entire shelf to form shelf‐edge deltas (Muto & Steel, 2002; Tagliaro et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…24 mya) and led to the drowning of the Andes foreland basin (Caputo & Soares, 2016) causing a series of marine incursions into the north portion of the Amazon basin, which later led to the formation of the Pebas Lake (Roddaz et al 2010, Hoorn et al 2022. The Pebas Lake was a wetland system that dominated the western Amazon during most of the Miocene (approximately from 23 to 10 mya) and isolated vast tracts of land, particularly the western portion of northern South America (Hoorn, 2010), with alternating periods of fresh and brackish water (Leandro et al 2022).…”
Section: Mechanisms Proposed To Explain Origins Of Diversity In the A...mentioning
confidence: 99%